The El arraiche mud volcano field at the Moroccan Atlantic slope, Gulf of Cadiz - Van Rensbergen, P
The El Arraiche field is a new mud volcano field discovered near the Moroccan shelf edge in the Gulf of Cadiz that consists of 8 mud volcanoes in water depths from 200 to 700 m. The largest mud volcano in the field (Al Idrissi mud volcano) is 255 m high and 5.4 km wide. The cluster was discovered during a survey with the RV Belgica and studied further during Leg 2 of the TTR 12 survey onboard the RN Prof Logachev. The 2002 surveys yielded detailed multibeam bathymetry over a 700 km(2) study area, dense grids of high-resolution seismic data, deep-tow sub bottom profiles, sidescan sonar mosaics over the major structures. Selected video imagery lines, video guided grab samples, dredge samples, gravity cores, and box cores were collected for groundtruthing purposes. Eight mud volcanoes in water depths from 200 to 700 in cluster around two, sub-parallel anticlines and associated active extensional faults. Rock clasts and regional seismic data locate the El Arraiche field over a Late Miocene-Pliocene extensional basin. The onset of mud volcanic activity is estimated at about 2.4 Ma and probably roots in the Cretaceous-Miocene accretionary wedge. Stacked outflows are visible up to a depth of about 500 in below the sea floor. The occurrence of long-lived mud volcanoes bear witness to continued overpressure generation at depth, either by in situ oil and gas generation or by focussed flow and accumulation in the area. Geochemical analyses of pore water from cores demonstrate the presence of thermogenic hydrocarbon processes. The activity of the mud volcanoes is indicated by the thickness of hemi-pelagic sediments covering extruded mud breccia, the occurrence of seep-typical fauna, the degree of mixing between thermogenic and biogenic hydrocarbon processes, or the depth to the base of the sulphate reduction zone. Given its structural setting and the evidence of thermogenic and biogenic hydrocarbons, the area has promising hydrocarbon potential but remains untested.